2020
DOI: 10.1371/journal.pone.0233435
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits of core self-evaluation as predictors on clinical decision-making in nursing profession

Abstract: Core self-evaluation (CSE) is a theory that includes four personality dimensions: selfesteem, self-efficacy, locus of control and emotional stability. CSE proved to be a significant predictor of the research on cognitive, emotional and behavioral responses across various situations in the workplace. The aim of this study was to examine the relationship between personality traits of the core self-evaluation and clinical decision-making in nurses' profession. A cross-sectional design was applied. Data was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 39 publications
3
27
0
4
Order By: Relevance
“…In contrast, neuroticism was negatively correlated with DCS. These results are supported by previous research [37,38] which found that anxious individuals with high levels of neuroticism are more likely to adopt emotional focus coping…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, neuroticism was negatively correlated with DCS. These results are supported by previous research [37,38] which found that anxious individuals with high levels of neuroticism are more likely to adopt emotional focus coping…”
Section: Discussionsupporting
confidence: 89%
“…There is evidence that Jordan University Hospital nurses have appeared personality trait of external locus of control than internal locus of control which explains that nurses depend on outer forces and abilities of other [ 30 ]. High perceived levels of CSE among nurses are mainly associated with better decision making, achieving goals, and improving performance in the workplace [ 31 ]. In contrast, low perceived levels of CSE are associated with lower satisfaction levels, lower control, and limited abilities [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the core self-evaluation domains, self-esteem domain is only found to be at high levels among participated nurses. This is indicative of improving self-control, performing effective health care, and successfully facing nursing tasks [ 31 ] which could lead to good self-esteem. This result is in line with the study of Alfuqaha et al [ 7 ], which also reported a moderate level of self-evaluation among nurses in Jordan.…”
Section: Discussionmentioning
confidence: 99%
“…The items in question are those which refer to aspects of the evaluation of self-respect and the influence of the profession. Since our participants are in the current progress of the educational process, it is possible that they identify their own professional self-respect with their own personal professional influence, and being students, they are still not in the position of completely developed feeling of self-respect ( Duruk et al, 2017 ), nor the feeling of possibility of professional influence ( Farčić et al, 2020 ). Such results may indicate the need to improve the practical part of education that would strengthen the mentioned aspects among nursing students.…”
Section: Discussionmentioning
confidence: 99%